2013
DOI: 10.1159/000348834
|View full text |Cite
|
Sign up to set email alerts
|

Brain Size and Morphology of the Brood-Parasitic and Cerophagous Honeyguides (Aves: Piciformes)

Abstract: Honeyguides (Indicatoridae, Piciformes) are unique among birds in several respects. All subsist primarily on wax, are obligatory brood parasites and one species engages in ‘guiding' behavior in which it leads human honey hunters to bees' nests. This unique life history has likely shaped the evolution of their brain size and morphology. Here, we test that hypothesis using comparative data on relative brain and brain region size of honeyguides and their relatives: woodpeckers, barbets and toucans. Honeyguides ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The possibility of brain reduction in social parasites has been explored in birds. The evolution of brood parasitism in birds was associated with reduced brain size in several clades, but the adaptive reasons for this pattern are not clear (Boerner & Kruger, ; Corfield et al ., ). Slave‐makers and their hosts are well suited to comparative analysis because slave‐makers are closely phylogenetically related to their hosts (Brady et al ., ; Moreau et al ., ; Buschinger, ).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of brain reduction in social parasites has been explored in birds. The evolution of brood parasitism in birds was associated with reduced brain size in several clades, but the adaptive reasons for this pattern are not clear (Boerner & Kruger, ; Corfield et al ., ). Slave‐makers and their hosts are well suited to comparative analysis because slave‐makers are closely phylogenetically related to their hosts (Brady et al ., ; Moreau et al ., ; Buschinger, ).…”
Section: Resultsmentioning
confidence: 99%
“…Data were compiled from the studies of Ebinger and Lohmer [1984], Corfield et al [2012b], Boire [1989], Cunningham et al [2013], Pistone et al [2002], Rehkamper et al [1991], Carezzano and Bee De Speroni [1995], Mehlhorn et al [2010], Fernandez et al [1997], and Alma and Bee De Speroni [1992]. Additional data on olfactory bulb size in California quail (Callipepla californica), black-winged stilt (Himantopus himantopus), South Island oystercatcher (Haematopus finschi), ostrich (S. camelus), and red-winged tinamou (R. rufescens) were obtained from the same specimens used in the studies of Cunningham et al [2013] and Corfield et al [2012c].…”
Section: Specimensmentioning
confidence: 99%
“…It is likely that all regions of a brain will shrink by the same amount, and therefore comparison of relative brain sizes reduces the amount of error when combining data from multiple studies [Corfield et al, 2012c]. Indeed, when comparing, for example, the size of the brain and the olfactory bulb in pigeons between the studies of Ebinger and Lohmer [1984] and Corfield et al [2012b], we found some differences in the sizes of both structures but the percentage of the telencephalon occupied by the olfactory bulb was nearly identical ( table 1 ).…”
Section: Specimensmentioning
confidence: 99%
“…However, there is also considerable residual variation in brain size around these allometric lines within and across various vertebrate groups, implying that brain size also depends on a nonsomatic component, which has been associated with a range of life history traits, such as parental investment, primary habitat, and feeding mode [Lefebvre et al, 2004;Yopak and Frank, 2009;Mull et al, 2011;Swanson et al, 2012;Corfield et al, 2013;Willemet, 2013;Tsuboi et al, 2015]. Previous studies on the allometric relationship between brain and body size have focused primarily on the gnathostomes, and thus relatively little is known about brain scaling in agnathans.…”
Section: Discussionmentioning
confidence: 99%